Threshold Effect of the Government Intervention in the Relationship Between Business Cycle and Population Health: Evidence From China - Chai, Kuang-Cheng; Yang, Yang; Cui, Zhen-Xin; Ou, Yang-Lu; Chang, Ke-Chiun (Frontiers in Public Health, 2021)
China is an emerging country and government intervention is always considered as an important part of the solutions when people facing challenges in China. Under the impact of the COVID-19 epidemic and the global economic downturn, the Chinese government quickly brought the epidemic under control and restored the positive economic growth through strong intervention. Based on the panel data of provincial level in China and the government intervention as the threshold variable, this paper empirically analyzed the non-linear effect of business cycle on population health by using the panel threshold regression model. The empirical results show that the impact of the business cycle on population health is significantly negative and government intervention has a single threshold effect on the relationship between business cycle and population health. When the government intervention is below the threshold value, the business cycle has a significant negative effect on the improvement of the population health level; when the level of government intervention exceeds the threshold value, the relationship between business cycle and population health becomes significantly positive. To some extent, the conclusions of this paper can guide the formulation and revision of government health policy, and help to adjust the direction and intensity of government intervention. The Chinese government and other governments of emerging countries should do more to harness the power of state intervention in their response to the business cycle.